Brand management : principles and practices - Dutta, Kirti (Oxford higher education, 2012)
"Brand management: principles and practices is a comprehensive textbook designed for post graduate management programmes students specializing in marketing. It explores core concepts of branding and illustrates them through numerous examples, exhibits, figures, images, case studies, and videos. Divided into five sections, first section gives an introduction to branding, creating a brand, and understanding how organizational culture helps in successful brand management. Second and third sections discuss brand equity, ways of researching and measuring it, and importance of understanding consumers and markets. Further, fourth section explains branding strategies, e-branding, and marketing communications. Last section explores brand architecture, brands over time, and boundary-less brands. Students will find this book useful for its illustrative coverage of the key concepts. The practical applications would also be very useful to practitioners."--Resumé vydavatele